-4-8=4(-3n+2)

Simple and best practice solution for -4-8=4(-3n+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-8=4(-3n+2) equation:


Simplifying
-4 + -8 = 4(-3n + 2)

Combine like terms: -4 + -8 = -12
-12 = 4(-3n + 2)

Reorder the terms:
-12 = 4(2 + -3n)
-12 = (2 * 4 + -3n * 4)
-12 = (8 + -12n)

Solving
-12 = 8 + -12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12n' to each side of the equation.
-12 + 12n = 8 + -12n + 12n

Combine like terms: -12n + 12n = 0
-12 + 12n = 8 + 0
-12 + 12n = 8

Add '12' to each side of the equation.
-12 + 12 + 12n = 8 + 12

Combine like terms: -12 + 12 = 0
0 + 12n = 8 + 12
12n = 8 + 12

Combine like terms: 8 + 12 = 20
12n = 20

Divide each side by '12'.
n = 1.666666667

Simplifying
n = 1.666666667

See similar equations:

| 9x-11=3x+8 | | 4x(3-y)=0 | | x+5(x-2)=8 | | 24+3x=3x(7-1) | | 9n+1=10 | | 10x=2+5 | | X-0.2x=520 | | 6x+29=-25 | | f(x)=x-(3/lnx) | | f(x)=x-3/lnx | | 18x-5x+4=28 | | 8x-(6x+5)=4x-21 | | 4x+2=(x-5) | | 4y+2=3(y-5) | | 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 | | 7*7*7*7*7=212 | | 7*5=212 | | 3t-9=7-1 | | 6x+3y=15.75 | | 7z-5-5(z+1)=-(4z+7) | | 1/3*4x | | 2k^2+7k-30=0 | | 7-q/4=2.5 | | 7-4=2.5 | | -3x+10y=0 | | sx+ty=ufory | | 8v=-18 | | 4lnx+6=0 | | 7(x+2)-8(4+3x)=47 | | 7(x-2)-8(4+3x)=47 |

Equations solver categories